Exchange Rate Pass-Through in ITF Adopting Countries: Indonesia, Thailand, Philippines Comparative Study - Fauziah, Syifa; Akhmad Syakir Kurnia (Universitas Negeri Semarang, 2024)
This paper investigates how the adoption of inflation targeting influenced Exchange Rate Pass-Through (ERPT) in the three developing countries of Southeast Asia – Indonesia, Thailand, and the Philippines. Moreover, this paper aims to analyze the macroeconomic determinants of the degree of pass-through to a consumer price index. For this purpose, we employ an Error Correction Model (ECM) regression analysis. The results found evidence that adopting an inflation-targeting framework does not necessarily reduce the degree of ERPT. However, economic openness emerges as a key limiting factor as higher trade share and lower trade tariffs lessen the degree of ERPT in those countries. It implies that trade liberalization, economic diversification, and enhancing competitiveness to reduce reliance on imports can further mitigate ERPT’s impact on inflation.